Effects of cigarette smoking and human T-cell leukaemia virus type 1 infection on anti-citrullinated peptide antibody production in Japanese community-dwelling adults: the Nagasaki Islands Study. (4th July 2021) - Kawashiri, S-y; Tsuji, Y; Tamai, M; Nonaka, F; Nobusue, K; Yamanashi, H; Maeda, T; Kawakami, A
Abstract : Objectives : We investigated whether the positivity of anti-citrullinated peptide antibody (ACPA) is associated with cigarette-smoking status and human T-cell leukaemia virus type 1 (HTLV-1) infection in a general population in Nagasaki, Japan, which is an ageing and HTLV-1-endemic area. Method : Baseline data from community-dwelling people in the Nagasaki Islands Study (NaIS) were included in this cross-sectional analysis. ACPA and HTLV-1 were measured in 3887 subjects without a history of treatment for rheumatoid arthritis. A logistic regression analysis was performed to assess the relationship between ACPA positivity and candidates of correlation with ACPA, i.e. the cigarette-smoking status quantified by Brinkman's index (BI) and HTLV-1 positivity. Results : Fifty-one subjects (1.3%) showed ACPA positivity, and 650 subjects (16.6%) were HTLV-1 carriers. In an age- and gender-adjusted logistic regression analysis, the BI [odds ratio (OR) 1.09, 95% confidence interval (CI)1.02–1.14, p = 0.0031] and a BI value > 500 (OR 3.92, 95% CI 1.72–9.22, p = 0.0014) were each significantly associated with ACPA positivity. HTLV-1 positivity did not show any association with ACPA positivity. Conclusion : A significant effect of cigarette-smoking status on ACPA production was revealed, whereas HTLV-1 positivity was not associated with ACPA production in this general population.